An evaluation of the effectiveness of the new primary school life sciences curriculum in practice - Gömleksiz, Mehmet Nuri; Bulut, Ilhami (My University, 2007)
The aim of this study is to determine the views of classroom teachers about the effectiveness of the new primary school Life Sciences curriculum in practice. For that aim, a 32-item Likert-type Life Sciences Curriculum Scale was developed. The population includes 784 classroom teachers working in 591 pilot schools in İstanbul, Ankara, İzmir, Kocaeli, Van, Hatay, Samsun and Bolu cities. The data were analyzed in terms of city, classroom, gender, teaching experience, education level and student number variables. Independent samples t test, Kruskal Wallis H test, variance analysis, Mann Whitney U, Scheffe and LSD tests were used to analyze the data. With the study, the learning attainments, content, teaching-learning activities and evaluation offered in the new Life Sciences curriculum were found effective in practice by the teachers. Statistically significant. differences were found among the views of the teachers in terms of city, and gender variables. The differences between male and female teachers should be searched and the gap among the physical equipment of the schools should be eliminated.
Yeni hayat bilgisi dersi ö?retim programinin uygulamadaki etkili?inin de?erlendirilmesi
Keywords: Constructivism; Curriculum evaluation; New primary school Life Sciences curriculum